Stress Level Differences on Final Year Nursing Students During Distance Learning Between Gender - Yustanti, Audy Savira; Sukartini, Tintin; Zulkarnain, Hakim (Universitas Airlangga, 2023)
Introduction: Implementing distance learning for final-year nursing students preparing their theses often adds significant burden and stress. Recognizing that stress levels can vary between male and female students is important. This study examines the differences in stress levels among final-year nursing students based on gender. Method: The study employed a comparative research design with a cross-sectional approach. A total of 167 final-year nursing students from the Bachelor of Nursing programs at Airlangga University and Nahdlatul Ulama University in Surabaya participated in the study. The researchers utilized a non-probability sampling technique, specifically purposive sampling. The independent variable in this study was gender, while the dependent variable was the stress level. The instrument used for data collection was the Depression Anxiety Stress Scale (DASS) 42 questionnaire, which employs a Likert scale. The data were analyzed using a paired T-test. Results: A significant proportion of students experiencing stress are female, accounting for 83.2% or 139 individuals. The most frequently observed stress level was mild, affecting 28.1% or 66 students. Furthermore, the comparative analysis revealed a notable difference in stress levels between male and female students in their final semester. Conclusions: The findings indicate a significant disparity in stress levels between male and female students, highlighting gender differences as a contributing factor to the variations in stress among the study subject.